2011
DOI: 10.1093/molbev/msr284
|View full text |Cite
|
Sign up to set email alerts
|

Selective Sweep of a cis-Regulatory Sequence in a Non-African Population of Drosophila melanogaster

Abstract: Although it is thought that changes in gene expression play an important role in adaptation, the identification of gene-regulatory sequences that have been targets of positive selection has proved difficult. Here, we identify a cis-regulatory element of the Drosophila melanogaster CG9509 gene that is associated with a selective sweep in a derived non-African population of the species. Expression analyses indicate that CG9509 consistently shows greater expression in non-African than in African strains of D. mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 56 publications
6
44
0
Order By: Relevance
“…(Catania et al, 2004;Karasov et al, 2010;Lynd et al, 2010;Saminadin-Peter et al, 2012). Through cloning and sequencing of the region upstream of CYP9M10 in field populations we have shown that sequence identical to that found in the ISOP450 strain can be found in Ghana, Malawi, Zambia and Uganda.…”
Section: Discussionmentioning
confidence: 69%
“…(Catania et al, 2004;Karasov et al, 2010;Lynd et al, 2010;Saminadin-Peter et al, 2012). Through cloning and sequencing of the region upstream of CYP9M10 in field populations we have shown that sequence identical to that found in the ISOP450 strain can be found in Ghana, Malawi, Zambia and Uganda.…”
Section: Discussionmentioning
confidence: 69%
“…One gene that shows a large and consistent expression difference between African and non-African flies of both sexes is CG9509 [9,41,44]. The specific function of this gene in D. melanogaster is unknown, although sequence homology has led to it being annotated as a choline dehydrogenase [45].…”
Section: (D) Population Genetics and Expression Of Cg9509mentioning
confidence: 99%
“…We find that sequence polymorphism is very low in all . The Zimbabwe and The Netherlands populations were used in a previous study of sequence and expression variation associated with the CG9509 enhancer region [44], as well as in previous genome-wide studies [29,35,36,47]. The Malaysian population also was used in previous genome-wide demographic studies [31,48].…”
Section: (D) Population Genetics and Expression Of Cg9509mentioning
confidence: 99%
See 2 more Smart Citations